2020
DOI: 10.1038/s41467-020-15126-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the gut microbiota on the m6A epitranscriptome of mouse cecum and liver

Abstract: The intestinal microbiota modulates host physiology and gene expression via mechanisms that are not fully understood. Here we examine whether host epitranscriptomic marks are affected by the gut microbiota. We use methylated RNA-immunoprecipitation and sequencing (MeRIP-seq) to identify N6-methyladenosine (m 6 A) modifications in mRNA of mice carrying conventional, modified, or no microbiota. We find that variations in the gut microbiota correlate with m 6 A modifications in the cecum, and to a lesser extent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 114 publications
(197 reference statements)
0
66
0
1
Order By: Relevance
“…Similar results have been shown at the organ level in which the microbiome has been reported to affect m 6 A level in brain, intestine, and liver. 29 The most significantly affected pathway is the NOTCH signaling pathway, which has been shown to regulate T cell homeostasis and differentiation. 30 It is not clear whether the dysbiosis leads to the inflammation or is a secondary phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown at the organ level in which the microbiome has been reported to affect m 6 A level in brain, intestine, and liver. 29 The most significantly affected pathway is the NOTCH signaling pathway, which has been shown to regulate T cell homeostasis and differentiation. 30 It is not clear whether the dysbiosis leads to the inflammation or is a secondary phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic reactions are reversible chromatin (gene and protein) alterations that occur in two forms, methylation and acetylations. With methylation, gene and chromatin structures are not available for transcription by replication enzymes; however, with acetylation of lysine or arginine residues in chromatin (histones), gene sequences are available to replication enzymes and transcription may occur [ 100 , 101 , 102 , 103 , 104 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. To help understand and these reactions, as well as epigenetic protocols, the reader is advised to consult the text edited by Tollefsbol [ 111 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
“…Another level of complexity is introduced when the presence of other bacterial species, such as the components of the microbiota, are considered. Recent advances in microbiome research have shown that the gut microbiota can influence intestinal homeostasis and immunity by modulating host epitranscriptomic [133] and epigenetic modifications [134][135][136]. Lm is known to produce bacteriocins that kill other bacteria to promote its own infection, therefore, it may also be able to affect the transcriptional profile of its host by targeting specific members of the host gut microbiome [137,138].…”
Section: Discussionmentioning
confidence: 99%